Perceptions of international strategic moves: Saudi Arabia versus the United States - C. J. Robertson; M. A. Yaghmour; E. H. Kawther (South African Journal of Business Management, 2015)
Competitive strategy is one of the most important activities that top management team members can undertake. In the global marketplace perceptions of strategic moves and plausible foreign markets to enter can vary based on cultural differences, economic conditions and past experiences. In this study we match the Miles and Snow strategic orientations with possible entry into different foreign markets. An in-depth survey of strategic orientation perceptions is developed and, based on a two-country research design, we obtain responses from 89 individuals from The United States and Saudi Arabia. A review of literature related to strategic orientation and cultural differences is performed and results suggest differences in perceptions of strategic preference and rating of promising foreign markets between the two national cohort groups. Three salient hypotheses are tested and supported related to topics such as where individuals prefer to invest, cultural distance and economic systems. Our differentiating contributions are (a) methodological, we use survey data rather than archival firm data as well as vignettes, and (b) theoretical, we assess managerial perceptions of foreign entry choice as opposed to firm level decisions. Managerial and future research implications are also discussed.
Keywords: 650